Pagoh Education Hub Shared Facilities Booking System: A Usefulness Survey - Abdul Aziz, Luqman Nul Hakim; Mazlan, Mohamad Afiq Afnan; Mohd Helmi, Mohamad Faris; Rahmat, Hazwani (Multidisciplinary Applied Research and Innovation, 2024)
Pagoh Education Hub shared facilities are a place where many facilities are provided for students and staff from public higher education institutions in Pagoh Education Hub. The Ministry of Higher Education (MOHE) is responsible for processing booking approvals and keeping them recorded. The main issue with the current booking process is that bookers must go to the Ministry of Higher Education office in Pagoh Edu Hub to request and fill in the booking form within office hours. The purpose of this system is to provide a systematic recording system for booking information, develop an alternative booking service for booking Pagoh Edu Hub shared facilities, and evaluate the system’s ease-of-use aspect. The methodology used for the development of this system is agile. This study conducted a feasibility survey among the bookers and discovered that the current booking process could be more efficient because the booking process needs to be done physically. The respondents agree that an online booking system should be created to simplify the booking process. Additionally, ease-of-use testing has been conducted using the USE Questionnaire with 33 students and one Pagoh Edu Hub staff to assess the system’s ease of use. The recommendations for the system are creating an Android or IOS version to make it easier for bookers to access using mobile phones and providing information regarding equipment provided in each facility.